Mental Coaching Pattern By Coaches in Increasing The Confidence of Koni Squash Athletes in Bandung City - Haris Abdurahman; Tedi Supriyadi; Aam Ali Rahman (Journal of Physical Education Health and Sport, 2026)
Mental factors play an important role in determining athlete performance; however, the mental development of squash athletes at the KONI Bandung City is still not fully structured, resulting in problems such as low self-confidence and competitive anxiety. This study aims to understand the mental coaching pattern of squash coaches of KONI Bandung City, the strategies used, and its impact on athletes' confidence with a qualitative approach of case study design through interviews, observations, and documentation on two coaches and eleven athletes. The results showed that mental coaching was carried out in an integrated manner with physical and technical aspects through humanist and adaptive approaches, such as match simulation, emotion regulation, personal communication, and self-talk. The observational findings showed optimal achievement in physical readiness and resilience (100%), while cognitive and motivational aspects were in the range of 54%–72%, which showed a variation in athletes' mental stability. In conclusion, structured and sustainable mental coaching is effective in increasing athletes' confidence and mental resilience, but it is still necessary to strengthen the cognitive aspects and mental independence so that athletes' performance is more stable and optimal.